Circular Anchors for the Detection of Hematopoietic Cells Using Retinanet - Grabel, Philipp; Ozkan, Ozcan; Crysandt, Martina; Herwartz, Reinhild; Baumann, Melanie; Klinkhammer, Barbara M.; Boor, Peter; Brummendorf, Tim H.; Merhof, Dorit (Proceedings - International Symposium on Biomedical Imaging, 2020)
Analysis of the blood cell distribution in bone marrow is necessary for a detailed diagnosis of many hematopoietic diseases, such as leukemia. While this task is performed manually on microscope images in clinical routine, automating it could improve reliability and objectivity. Cell detection tasks in medical imaging have successfully been solved using deep learning, in particular with RetinaNet, a powerful network architecture that yields good detection results in this scenario. It utilizes axis-parallel, rectangular bounding boxes to describe an object's position and size. However, since cells are mostly circular, this is suboptimal. We replace RetinaNet's anchors with more suitable Circular Anchors, which cover the shape of cells more precisely. We further introduce an extension to the Non-maximum Suppression algorithm that copes with predictions that differ in size. Experiments on hematopoietic cells in bone marrow images show that these methods reduce the number of false positive predictions and increase detection accuracy.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Bone Marrow; Cell Detection; RetinaNet